Agriculture Study Program Students’ Needs in Learning English at Sintuwu Maroso University - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2021)
The objective of this research is to find out the students’ needs in Learning English for Agriculture Study Program at Sintuwu Maroso. The data collected by questionnaire. The data is analyzed by percentage formula. The finding of the research obtain that the students need in learning English for agriculture is to support their study.  The most important skill is reading and speaking.  The students need to learn English without working in small group because often have difficulty working in a small group during the class and the students need to understanding the lecture speaking because have trouble in understanding lecturers words. The students need to say something in English but always worry about saying something in case make a mistake in English. Students’ needs in improving their communication effectively with peers. It means that the students need in learning English for agriculture is to mastery in speaking